Flora and vegetation of the National Reserve Lago Peñuelas, Biosphere Reserve, Region of Valparaiso, Chile - Hauenstein, Enrique; Muñoz-Pedreros, Andrés; Yánez, José; Sánchez, Pamela; Möller, Patricia; Guiñez, Basilio; Gil, Claudia (Bosque (Valdivia), 2009)
The National Reserve Lago Peñuelas belongs to the National System of Protected Wild Areas, located in the Region of Valparaiso, Chile. This unit, together with the National Park La Campana, constitutes a Biosphere Reserve. The flora and vegetation of the National Reserve was studied. The study registered 163 species of vascular plants, of which 48 are new records. Considering the studies and previous reports made in situ, the floristic richness reaches 337 species, of which 72% are native; eight of them are pteridophytes, two are gimnospermae, 229 are dicotyledoneae and 98 are monocotyledoneae. This represents a high floristic diversity. Nevertheless, the high proportion of aloctonous plants indicates a relative high degree of anthropic disturbance. Fourteen species have conservation problems (two of them are threatened, eleven are vulnerable and one is data deficient). The total phytosociology of the place reports the presence of 20 plant communities, ten of which are herbaceous, seven scrub and three tree communities; of these, 12 have already been described in previous works, adding the present study eight new associations for the place. It is proposed to keep as restricted areas the sector of Los Lirios, which contains most of the threatened species, and the sector of Vega del Alamo, because of its valuable condition as a relict of the hygrophilous forest present.